Determining the Trade Value of Indonesian Lobster Exports to Destination Countries in 2018–2023 - Herlina, Azizah Pingki; Lestari, Wuryaningsih Dwi (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the effect of financial management on profitability in small and medium enterprises (SMEs) producing woven bags in Sukowiyono Village, Ngawi. Financial management variables are measured using Break Even Point (BEP) and profit margin, while profitability is proxied by Return on Assets (ROA), gross profit, and net profit. The research method employs a quantitative approach with multiple linear regression analysis processed through SPSS. The results show that simultaneously, BEP and profit margin have no significant effect on ROA profitability; however, partial tests indicate that BEP has a significant negative effect, while profit margin has a significant positive effect. These findings suggest that BEP functions as a cost planning tool, whereas profit margin is the dominant factor in increasing profit. Analysis of net profit also reveals that profit margin contributes more significantly than BEP to improving profitability. Although the research model is able to explain almost all variations in profitability, there are external factors not included in the analysis. The limitations of this study include the use of only one SME as the research object and a relatively short data period. Therefore, future research is expected to cover more SMEs and include additional variables to produce more representative results.